Perkembangan Logistik Halal - Febriyanni, Rani (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2022)
Halal products' integrity is upheld when halal practices are consistently implemented throughout the storage process within uncontaminated warehouses, utilizing hygienic transportation methods for transferring goods from warehouses to stockpiles, and ensuring that packaging and marketing prevent exposure to impurities. The entire supply chain involved must adhere to halal standards, and LPPOM MUI facilitates this by issuing halal certifications that encompass logistics, guaranteeing halal practices. Among the tools available, logistics companies can adopt the SJH framework. This paper aims to elucidate the imperative for halal logistics, establishing an assurance that the halal status is unwaveringly preserved across all logistical operations and their associated supply chains, mitigating the risk of transgression into non-halal domains. Employing qualitative research methods, this study unveils that beyond products exclusively meant for Muslim consumption under Sharia, logistics itself demands meticulous attention. Thus, logistics operations aligned with Sharia principles emerge as a requisite. Adherence to these principles within logistics will safeguard the sanctity of halal products, ensuring their purity throughout the journey—from raw materials and packaging to storage and transportation—preventing any amalgamation with non-halal entities.